Study of clinical presentation of falciparum malaria and correlation with laboratory indices of poor prognosis - Choudhary, Hazarimal; Choudhary, Prema Ram (International Journal of Advances in Medicine, 2017)
Background: Severe malaria is a chief cause of death in the North-eastern states of India. The criteria for defining severe malaria have fluctuating over the last many years. Detection of both specific and sensitive clinical features of falciparum malaria to predict death is required to improve clinical management. Therefore, the objective of present study was designed to investigate the clinical presentation of falciparum malaria and correlation with laboratory indices of poor prognosis. Methods: This prospective observational study was conducted at the R N T Medical College Udaipur, India. Total 53 malarial patients who tested positive for plasmodium falciparum were included. A detailed clinical presentation, haematological and biochemical variables were scrutinized. SPSS-16 software was used for statistical analysis. Results: Out of 53 patients, 6 (11.3%) patients had (>5%) parasitaemia, 3 (5.66%) patients had schizonts in peripheral blood film, 2 (3.77%) patients had serum creatinine >3.0 mg%, 4 (7.54%) patients had raised SGOT and SGPT and all have been died while 11 (20.75%) patients had haemoglobin <7.1 gm% and amongst these 3 (27.27%) patients were died. Out of 53 patients, 13 patients (24.53%) died. Most of the patients had over lapping features with anemia (13.32%), ARDS, 16.98 %, Jaundice 9.43% and impaired consciousness (32.96%). These four features were responsible for high incidence of mortality in malaria. Conclusions: Decisively 29 (54.71%) patients were having laboratory indices of poor prognosis and amongst them 19 (65.51%) patients were died. Therefore, our findings confirm that patients who had P. falciparum malaria with laboratory indices of poor prognosis had high incidence of mortality.